Circulating Tumor Cells, DNA, and mRNA: Potential for Clinical Utility in Patients With Melanoma. (27th November 2015) - Xu, Melody J.; Dorsey, Jay F.; Amaravadi, Ravi; Karakousis, Giorgos; Simone, Charles B.; Xu, Xiaowei; Xu, Wei; Carpenter, Erica L.; Schuchter, Lynn; Kao, Gary D.
Abstract: Circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and messenger RNA (mRNA), collectively termed circulating tumor products (CTPs), represent areas of immense interest from scientists' and clinicians' perspectives. In melanoma, CTP analysis may have clinical utility in many areas, from screening and diagnosis to clinical decision-making aids, as surveillance biomarkers or sources of real-time genetic or molecular characterization. In addition, CTP analysis can be useful in the discovery of new biomarkers, patterns of treatment resistance, and mechanisms of metastasis development. Here, we compare and contrast CTCs, ctDNA, and mRNA, review the extent of translational evidence to date, and discuss how future studies involving both scientists and clinicians can help to further develop this tool for the benefit of melanoma patients. Abstract : In melanoma, analysis of circulating tumor products (CTPs) may have clinical utility in areas such as screening, diagnostics, and clinical decision-making, and may serve as surveillance biomarkers or sources of real-time genetic or molecular characterization. CTP analysis reveals new biomarkers, patterns of treatment resistance, and mechanisms of metastasis development. This report compares and contrasts CTPs, reviews the translational evidence to date, and discusses how CTP research can benefit patients with melanoma.